2011
DOI: 10.1007/s10750-011-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal zooplankton dynamics in main channel and backwater habitats of the Upper Mississippi River

Abstract: This study used stratified random sampling to examine the spatial and temporal distribution of zooplankton communities in a large floodplain river (Mississippi River, USA). Potential mechanisms controlling zooplankton abundance and community structure were considered. Main channel and backwater habitats included in this study differed between a turbid upper pool reach where aquatic macrophytes were sparse and a lower pool reach which was considerably less turbid and had extensive aquatic macrophyte coverage. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 66 publications
(87 reference statements)
2
39
1
1
Order By: Relevance
“…She showed that zooplankton abundances were significantly higher in a backwater than they were in the mainstem for most sampling periods. With respect to other large rivers, Burdis and Hoxmeier (2011) reported that zooplankton were more abundant in Mississippi River backwaters than they were in main channel habitats. They attributed these differences in zooplankton to longer residence times, higher levels of primary production, and/or increased water clarity in backwaters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She showed that zooplankton abundances were significantly higher in a backwater than they were in the mainstem for most sampling periods. With respect to other large rivers, Burdis and Hoxmeier (2011) reported that zooplankton were more abundant in Mississippi River backwaters than they were in main channel habitats. They attributed these differences in zooplankton to longer residence times, higher levels of primary production, and/or increased water clarity in backwaters.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of suspended sediment and higher discharge can in turn negatively impact zooplankton. In particular, larger-bodied taxa such as cladocerans and copepods tend to be more abundant in riverine habitats with slower velocities, lower turbulence, lower turbidity, and longer residence times (Sluss et al 2008;Burdis and Hoxmeier 2011). High concentrations of suspended solids can clog zooplankton filtering appendages, decrease feeding rates, and reduce overall growth rates (McCabe and O'Brien 1983;Kirk and Gilbert 1990;Soeken-Gittinger et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Community structure of phytoplankton and zooplankton is strongly influenced by TSS and connectivity with lentic areas (Wahl et al 2008, Burdis and Hoxmeier 2011, Manier 2014. Current velocity and substrate type within the channel influence the distribution of benthic invertebrates (Fremling 1960, Seagle et al 1982, Anderson and Day 1986, Dettmers et al 2001b, and connectivity with adjacent lentic areas provides important sources of invertebrate drift (Eckblad et al 1984, Sheaffer andNickum 1986b).…”
Section: Fish Communitymentioning
confidence: 99%
“…In late spring and summer, backwater habitats often have increased water residence time, low velocities, shallow depths, food resources, and warm temperatures that are important for growth and development of larval fish Nickum 1986a, Nannini et al 2012). Backwaters generally support diverse phytoplankton, zooplankton, and macroinvertebrate communities that serve as important food sources for larval and adult fishes (Eckblad et al 1984, Sheaffer and Nickum 1986b, Wahl et al 2008, Burdis and Hoxmeier 2011, Ochs et al 2013, though these food sources can be influenced by water level variability and substrate composition (Flinn et al 2008). Submersed vegetation and other forms of structural complexity, such as coarse woody debris, provide protection from predation (Dewey et al 1997) and promote growth (Richardson et al 1998) and abundance of certain young-of-year species (DeLain and Popp 2014).…”
Section: Fish Communitymentioning
confidence: 99%
“…fitted with a stop-valve near the bottom. Tube samplers collect integrated samples throughout the water column that provide zooplankton densities comparable to other sampling devices (Lewis & Saunders, 1979;DeVries & Stein, 1991), and have commonly been used to sample shallow lake and wetland habitats (e.g., Parkos et al, 2003;Lemke & Benke, 2009;Schuyler et al, 2009;Burdis & Hoxmeier, 2011). This sampling approach was used consistently during this study to quantify zooplankton in these shallow, vegetated floodplain lakes in order that samples could be compared between sites and within each site over time.…”
Section: Zooplanktonmentioning
confidence: 99%